SYSTEMATIC LITERATURE REVIEW: THE EFFECT OF DZIKIR ON THE MENTAL HEALTH OF NURSES : TINJAUAN PUSTAKA SISTEMATIS: PENGARUH DZIKIR TERHADAP KESEHATAN MENTAL PERAWAT - Radha, Andi; Mallapiang, Fatmawaty; Habibi (Universitas Islam Negeri Alauddin Makassar, 2025)
Background: Mental health of nurses become issue crucial in the middle height pressure work in critical units like room emergency emergency department (ER) and intensive care unit (ICU). Method : Research This use method Systematic Literature Review (SLR) with through two processes , namely the review process and the identification process journal with systematic use Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA) guide Result: Based on search journal relevant articles​ with mental health in nurses obtained 149 journals sourced articles​ from publications in Science Direct, PubMed, and Google Scholar which were then filtered Then after screening with notice title , keywords , and access journal article the obtained 35 journals articles and produce 5 relevant articles​ with topic study . Conclusion: Results Practice dhikr as therapy relaxation psychospiritual proven effective in reduce level anxiety and stress in nurses . Home hospitals and institutions health recommended develop training programs therapy dhikr in a way professional as part from the improvement strategy mental health of nurses in a way sustainable